1998
DOI: 10.2172/9919
|View full text |Cite
|
Sign up to set email alerts
|

The Standard Model and Why We Believe It

Abstract: The principle components of the Standard Model and the status of their experimental verification are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
0
15
0
4
Order By: Relevance
“…The third generation lepton masses are all close to 600 GeV, Mτ 1 = 599 GeV, Mτ 2 = 617 GeV, Mν τ = 610 GeV. These processes have previously been considered in [15,30].…”
Section: Resonant Slepton Productionmentioning
confidence: 69%
See 2 more Smart Citations
“…The third generation lepton masses are all close to 600 GeV, Mτ 1 = 599 GeV, Mτ 2 = 617 GeV, Mν τ = 610 GeV. These processes have previously been considered in [15,30].…”
Section: Resonant Slepton Productionmentioning
confidence: 69%
“…However given the limits on this coupling this signal will only be visible above the background at the highest couplings currently allowed by low energy experiments. In [15,30] it was suggested that by using the sidebands to normalize the background that resonant slepton production could be probed to much smaller values of the couplings. Indeed the S/ √ B numbers in Fig.…”
Section: Requiring the Two Leading Jets In E T To Be Back To Back ||φmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional contributions to CP violation via loop diagrams appear in some extensions of the SM [109,110,111,112,113,114,115,116] and can result in these asymmetries within experimental reach. In experimental measurements the muon is much easier to identify than any other lepton, therefore all experimental results on the semileptonic charge asymmetry are obtained with l = µ in Eq.…”
Section: Cp Asymmetry In Mixing Of Neutral B Mesonsmentioning
confidence: 99%
“…As such it is important to search for new sources of CP V beyond the SM. The B 0 s system is one possible source, since the effects of CP V are expected to be small in the SM [4], and can be significantly enhanced by new physics models [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%